Marked gender differences in progression of mild cognitive impairment over 8 years. Issue 2 (21st July 2015) - Lin, Katherine A.; Choudhury, Kingshuk Roy; Rathakrishnan, Bharath G.; Marks, David M.; Petrella, Jeffrey R.; Doraiswamy, P. Murali; ,
Abstract: Introduction: This study examined whether, among subjects with mild cognitive impairment (MCI), women progressed at faster rates than men. Methods: We examine longitudinal rates of change from baseline in 398 MCI subjects (141 females and 257 males) in the Alzheimer's Disease Neuroimaging Initiative‐1, followed for up to 8 years (mean, 4.1 ± 2.5 years) using mixed‐effects models incorporating all follow‐ups (mean, 8 ± 4 visits). Results: Women progressed at faster rates than men on the Alzheimer's disease assessment scale‐cognitive subscale (ADAS‐Cog; P  = .001) and clinical dementia rating‐sum of boxes (CDR‐SB; P  = .003). Quadratic fit for change over time was significant for both ADAS‐Cog ( P  = .001) and CDR‐SB ( P  = .004), and the additional acceleration in women was 100% for ADAS‐Cog and 143% for CDR‐SB. The variability of change was greater in women. The gender effect was greater in apolipoprotein E ( APOE ) ε4 carriers. Discussion: Women with MCI have greater longitudinal rates of cognitive and functional progression than men. Studies to confirm and uncover potential mechanisms appear to be warranted. Trial Registration: ADNI ClinicalTrials.gov identifier: NCT00106899 .